Defective proteostasis in patient‐derived iPSC astrocytes and neurons carrying a MAPT IVS10+16 mutation. (December 2021) - Mahali, Sidhartha; Martinez, Rita; Hu, Miwei; Marsh, Jacob; Temple, Sally; Karch, Celeste M.
Abstract: Background: Impaired proteostasis is associated with normal aging and is accelerated in neurodegeneration. This impairment may lead to the toxic accumulation of protein. In a subset of frontotemporal dementia (FTD) cases, mutations in the microtubule‐associated protein tau ( MAPT ) that alter the relative levels of tau isoforms are sufficient to cause tau inclusions in neurons and astroglia and neurodegeneration without the presence of mutated protein (e.g. MAPT IVS10+16). However, the pathogenic events triggered by the expression of the alternatively spliced tau remain poorly understood. Method: To determine whether altered tau splicing induced from MAPT IVS10+16 mutations is sufficient to alter proteostasis in neurons and glia, we used human induced pluripotent stem cell (iPSC)‐derived neurons and astrocytes from patients carrying the MAPT IVS10+16 mutation and CRISPR/Cas9, isogenic corrected controls. Result: We found that neurons from MAPT IVS10+16 carriers exhibited significantly higher levels of tau containing 4 microtubule binding repeats (4R tau), deficits in lysosomal trafficking, and acidity relative to isogenic‐control neurons. Conversely, astrocytes from MAPT IVS10+16 carriers exhibited morphologically an increase in acidic lysosomes compared to isogenic‐control astrocytes. Astrocytes from MAPT IVS10+16 carriers were also larger in size, consistent with cellular hypertrophy observed in brains from FTD‐tau patients. Conclusion: Our findings suggest that altered tau splicing induced by the MAPT IVS10+16 mutation is sufficient to cause impaired lysosomal function and altered proteostasis in a cell‐type specific manner.